The mortality of infants in Lima in 1918 - Eyzaguirre, Rómulo (1920)
In 1908, a study of the mortality of infants in Lima, observed in summary, the following, in respect of birth: 1 .- From 1884-1904, the number of legitimate births is 47% and the 53% illegitimate without hereafter has been significantly altered this conclusion. 2 .- The illegitimate birth rate in Lima, is greater than in Buenos Aires, Montevideo, Santos (Brazil), Santiago de Chile, Valparaiso, Mexico and many cities in the United States and European states. It is only less than that of San Salvador, which reaches 68%. 3 .- Indigenous produce more legitimate, and then follow the white mestizos. 4 .- Indigenous produce the largest number of illegitimate, then mestizos and whites soon. It is, however, Indians are the most prolific, fleeing or not fleeing unless paternity. This is a general demographic observation; called inferior races, and less subject to economic, leave demotic better income.